2021
DOI: 10.25259/apos_14_2021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between objective evaluation and subjective evaluation of facial profile in skeletal Type II females

Abstract: Objectives: The objective of this study was to find the cephalometric measurements that correlate with the visual perception. Materials and Methods: A total of 250 lateral cephalograms of patients from the year 2016 to 2018 were hand traced and analyzed. Thirty-six hard- and soft-tissue measurements were obtained from the lateral cephalometric analysis. Silhouettes obtained from cephalometric films were rated by 10 orthodontists based on their level of convexity. For each sample, the rating of visual percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, the wide range of intraexaminer reliability, including one negative value, suggests that the judgments on facial profile of the same layperson tend to be variable and subjective at different occasions, although the same profile feature was evaluated. Our result contrasts with that of Lersinghanart et al (2020) 22 and Choki et al (2021) 29 who reported good correlation between H angles and visual perception. These differences can be explained in part by the difference in our study sample being recruited, in which laypersons were selected instead of orthodontic postgraduate students 22 and orthodontic specialists 29 who had orthodontic knowledge.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the wide range of intraexaminer reliability, including one negative value, suggests that the judgments on facial profile of the same layperson tend to be variable and subjective at different occasions, although the same profile feature was evaluated. Our result contrasts with that of Lersinghanart et al (2020) 22 and Choki et al (2021) 29 who reported good correlation between H angles and visual perception. These differences can be explained in part by the difference in our study sample being recruited, in which laypersons were selected instead of orthodontic postgraduate students 22 and orthodontic specialists 29 who had orthodontic knowledge.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was in agreement with Lersinghanart et al (2020), 22 ALBarakati and Bindayel (2012), 27 and Panezai et al (2021) 28 who reported that the mean values of the H angles were 15.27, 15.16, and 15.05 degrees, respectively. However, our mean H angle value was different with Choki et al (2021) 29 and Noviaranny et al (2022), 30 with a mean value of 20 and 10 degrees, respectively. H angle soft tissue is influenced by the thickness and position of the lips and the nose.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations